1994
DOI: 10.1139/m94-057
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic diversity of Rhizobium isolated from chickpea (Cicer arietinum L.)

Abstract: The diversity of 16 strains of chickpea-infective rhizobia from various geographical origins was analysed using genotypic and phenotypic approaches. Multilocus enzyme electrophoresis was performed, and restriction fragment length polymorphisms of the amplified 16S + IGS (intergenic spacer) rRNA gene, assimilation of 147 carbon sources, antibiotic resistance, and tolerance to NaCl and extreme pH values and temperatures were tested. These approaches had different discriminating powers. Esterase polymorphisms gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
63
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 27 publications
15
63
1
Order By: Relevance
“…The isolates changed YEMA-BTB medium to yellow and deep yellow were categorized as fast growing and others which changed to moderate yellow and did not show any color change were considered as a slow growing rhizobia. Chickpea rhizobia was reported to have both fast and slow growing strains (Nour et al, 1994). Moreover, isolates obtained from chickpea nodules failed to grow on BTB-medium (Wei et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The isolates changed YEMA-BTB medium to yellow and deep yellow were categorized as fast growing and others which changed to moderate yellow and did not show any color change were considered as a slow growing rhizobia. Chickpea rhizobia was reported to have both fast and slow growing strains (Nour et al, 1994). Moreover, isolates obtained from chickpea nodules failed to grow on BTB-medium (Wei et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen strains were compared by using multilocus enzyme electrophoresis, restriction fragment length polymorphism (RFLP) of the 16s rRNA gene, and more than 150 phenotypic characteristics (33). The results of all of the approaches were very consistent, and our data resulted in the delineation of two phylogenetically distant groups (groups A and B) and correlated relatively well with strain generation times (slow and fast growers).…”
mentioning
confidence: 76%
“…In order to reexamine the biodiversity of the chickpea rhizobia, we tested some of the collection strains used by Cadahia et al (5); the strains used were chosen to represent various geographical origins (33). Sixteen strains were compared by using multilocus enzyme electrophoresis, restriction fragment length polymorphism (RFLP) of the 16s rRNA gene, and more than 150 phenotypic characteristics (33).…”
mentioning
confidence: 99%
“…The data are in agreement with our recent report of Rhizobium tolerant to such a high pH value (Surange et al, 1997 a Overnight-grown (14-16 h) Rhizobium isolates (2-3ϫ10 9 cfu/ml) were incubated on a reciprocal shaker at the specified temperature forance range for Rhizobiaceae has been reported to be up to 9.5 (Jordan, 1984). Nour et al (1994) have reported pH tolerance of Rhizobium isolated from chickpea (Cicer arietinum L.) to be 10.0 and Shenbagarathai (1993) has reported Sesbania procumbens Rhizobium SBS-R100 capable of growing at pH 11.0.…”
Section: Survival Of Rhizobia At High Salt and Phmentioning
confidence: 99%